FORMULASI DAN UJI IRITASI SEDIAAN MASKER PEEL OFF GEL KOMBINASI EKSTRAK ETANOL BUNGA TELANG (Clitoria ternatea L.) DAN KUNYIT PUTIH (Curcuma zedoaria) - Putri, Safira Amalia; Annisa Fatmawati; Eva Nurinda; Didik Yuni Prasetya (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Butterfly pea flower (Clitoria ternatea L.) and white turmeric (Curcuma zedoaria) have antioxidant activity and can be combined to make a peel off gel mask. To ensure the quality and safety of the peel off gel mask, it is necessary to evaluate its physical properties and test for irritation. The manufacturing process involves extracting butterfly pea flower and white turmeric using a maceration method using 70% ethanol solvent. The resulting extract was tested for phytochemistry to identify alkaloids, saponins, flavonoids and tannins. The preparation was formulated with variations in extract concentrations: FI (1:3), FII (2:2) and FIII (3:1). Evaluation of physical properties includes organoleptic tests, pH, spreadability, homogeneity, stickiness, drying time and viscosity. Irritation tests were carried out on New Zealand rabbits. The result indicated that the peel off gel mask with various extract concentrations met most of the physical property evaluation requirements even though the pH test did not meet the standards. The EEBT and EEKP combination peel off gel mask did not cause irritation in New Zealand rabbits during 72 hours of observation.